Views of democracy and society and support for political violence in the USA: findings from a nationally representative survey - Garen J. Wintemute; Sonia L. Robinson; Andrew Crawford; Daniel Tancredi; Julia P. Schleimer; Elizabeth A. Tomsich; Paul M. Reeping; Aaron B. Shev; Veronica A. Pear (BMC, 2023)
Abstract Background Current conditions in the USA suggest an increasing risk for political violence. Little is known about the prevalence of beliefs that might lead to political violence, about support for and personal willingness to engage in political violence, and about how those measures vary with individual characteristics, lethality of violence, political objectives that violence might advance, or specific populations as targets. Methods This cross-sectional US nationally representative survey was conducted on May 13 to June 2, 2022, of adult members of the Ipsos KnowledgePanel. Outcomes are weighted, population-representative proportions of respondents endorsing selected beliefs about American democracy and society and violence to advance political objectives. Results The analytic sample included 8620 respondents; 50.5% (95% confidence interval (CI) 49.3%, 51.7%) were female; and weighted mean (± standard deviation) age was 48.4 (± 18.0) years. Nearly 1 in 5 (18.9%, 95% CI 18.0%, 19.9%) agreed strongly or very strongly that "having a strong leader for America is more important than having a democracy"; 16.2% (95% CI 15.3%, 17.1%) agreed strongly or very strongly that "in America, native-born white people are being replaced by immigrants," and 13.7% (95% CI 12.9%, 14.6%) agreed strongly or very strongly that "in the next few years, there will be civil war in the United States." One-third of respondents (32.8%, 95% CI 31.7%, 33.9%) considered violence to be usually or always justified to advance at least 1 of 17 specific political objectives. Among all respondents, 7.7% (95% CI 7.0%, 8.4%) thought it very or extremely likely that within the next few years, in a situation where they believe political violence is justified, "I will be armed with a gun"; 1.1% (95% CI 0.9%, 1.4%) thought it very or extremely likely that "I will shoot someone with a gun." Support for political violence and for the use of firearms in such violence frequently declined with increasing age, education, and income. Conclusions Small but concerning proportions of the population consider violence, including lethal violence, to be usually or always justified to advance political objectives. Prevention efforts should proceed urgently based on the best evidence available.